Profil Pendonor Darah Sukarela Saat Bulan Ramadhan - Ayu Kartika, Astri Dewi; Putri, Adita Puspitasari Swastya (Poltekkes Kemenkes Semarang, 2023)
During the month of Ramadan, people choose not to donate blood, because they do not know that blood donation is allowed and does not interfere with fasting activities. The amount of blood available at the beginning of the month of Ramadan at Blood Donation Unit in Indonesian Red Cross Rembang Regency accumulated as many as 373 bags of blood. The availability is only sufficient to meet the availability of needs for the first week during the month of Ramadan. The Purpose of the research is to describe the profile of voluntary blood donation during the month of Ramadan 2018 – 2020 at at Blood Donation Unit in Indonesian Red Cross Rembang Regency, The method of the research is This type of quantitative descriptive research, with a retrospective research design, and the Quota Sampling research technique, uses the solvin formula ,the sample for the 2018 sampling quota is 85 samples, in 2019 90 samples, and in 2020 85 samples, The results showed that the most voluntary blood donation during the month of Ramadan were male as much as 85.5%, the blood group of the most blood donation was blood type O Positive as much as 45,7%, the highest blood pressure category of blood donaton, namely 86,0% of pre-hypertensives and 98,8% of voluntary blood donation live in Rembang.